ISLAMIC EDUCATION MODEL ORIENTED ON THE VIEWS OF ACEH ULAMA ON CUSTOM SANCTIONS FOR COMMUNITIES FOR VIOLATION OF QANUN JINAYAT IN THE DISTRICT ACEH TAMIANG - Musthafa, Musthafa; Asmuni, Asmuni; Fuad, Zainul (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This research looks at what Acehnese scholars think about the customary punishments for people who break the khalwat qanun in Aceh Tamiang District, based on Aceh Province Qanun Number 6 of 2004 about Jinayat Law in the progressive Islamic education model. This research method is normative and empirical. It looks at legal principles and norms in laws and regulations, legal doctrine, and how legal norms are used in society. It then looks at the problem from the point of view of Acehnese scholars regarding violations of the khalwat qanun. The results of the study show that when putting customary life into practice, regions can set up different policies to help adat and traditional institutions in their areas that are based on Islamic law and work in line with it. Gampong or village residents who break the khalwat or make the Sharia look bad can first go to a Gampong Traditional Meeting (RAG). One reason why khalwat offenders aren't caned in Aceh Tamiang is because the case was settled in a way that was unfair to both local elites and the general public. A number of Khalwat cases were resolved through customary mechanisms. Sanctions such as the